2010
DOI: 10.7748/nr2010.04.17.3.17.c7742
|View full text |Cite
|
Sign up to set email alerts
|

Storytelling: an approach that can help to develop resilience

Abstract: Stories convey values and emotions, and can reveal the differences and similarities between people's experiences. Elucidating personal stories involves sharing which can help form bonds and supportive networks. With reflection, these can help to develop resilience. While the literature recognises the potential cathartic and therapeutic benefits associated with storytelling in research, links between the development of personal resilience and storytelling for research purposes have not been drawn. This paper ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 111 publications
(94 citation statements)
references
References 31 publications
0
80
0
2
Order By: Relevance
“…Some researchers also describe the impacts of storytelling on the development of personal resilience (East et al 2010). For individuals, chances to enhance adaptive capacity are promoted through engagement in various experiences accompanied by reflectivity, and a community with such competent individuals possibly has a higher adaptive capacity (Fazey et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers also describe the impacts of storytelling on the development of personal resilience (East et al 2010). For individuals, chances to enhance adaptive capacity are promoted through engagement in various experiences accompanied by reflectivity, and a community with such competent individuals possibly has a higher adaptive capacity (Fazey et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Narrative enquiry and analysis have been positioned under the realms of qualitative research. While it is recognised that there are differing strands of narrative analysis, there are several works which have suggested that narrative and story are indeed the same concept, which are, and can be used interchangeably (East, Jackson, O'Brien, & Peters, 2010;Polkinghorne, 1988). The notion of the 'narrative' 295 or 'story' is not new, as Czarniawska (2004) articulated.…”
Section: Methodsmentioning
confidence: 99%
“…Narrative inquiry highlights that all human experiences are meaningful (Polkinghorne, 1988); narratives are used by all groups within society to express experiences, cultural values, and interpretations (Czarniawska, 2004;Daiute & Light-foot, 2004). Narrative inquiry methods provide the opportunity for participants to tell their story, which has been identified as a potentially cathartic process (East, Jackson, O'Brien, & Peters, 2010). Further, listening to their stories attributes value to participants (Frank, 1995).…”
Section: Designmentioning
confidence: 99%